THE EFFECTS OF STOCK REPURCHASE ON THE MARKET VALUE AND ON THE COMPANY'S FINANCIAL POSITION OF DAIRIES IN SERBIA - Pavlović, Vladan; Muminović, Saša; Grbić, Vladimir (Economics of Agriculture, 2011)
This paper aims to show how the stock repurchase, aimed at preventing demage for company, was reflected on the stock price and financial position of companies of Serbian dairy industry. The choice of companies in the dairy industry is the result of significance of dairy industry for the Serbian economy and relatively significant stock repurchase of these companies in relation to the stock repurchase of companies in other sectors. Research on effects of stock repurchase on the market value indicated that the stock repurchase did not prevent a further decline in their value, as well as the numerous other anomalies of the Serbian capital market.